Analysis of combined data sets yields trend estimates for vulnerable spruce-fir birds in northern United States. (July 2015) - Ralston, Joel; King, David I.; DeLuca, William V.; Niemi, Gerald J.; Glennon, Michale J.; Scarl, Judith C.; Lambert, J. Daniel
Highlights: Point count surveys with disparate protocols combined to estimate population trends. Significant declines detected for 50% of spruce-fir forest birds. Spruce-fir obligates more likely to decline than associates. Significant declines in threatened species as well as species of "Least Concern". Trends significantly differed between Midwestern and Eastern US for 5 species. Abstract: Continental-scale monitoring programs with standardized survey protocols play an important role in conservation science by identifying species in decline and prioritizing conservation action. However, rare, inaccessible, or spatially fragmented communities may be underrepresented in continental-scale surveys. Data on these communities often come from decentralized, local monitoring efforts that differ in their goals and survey protocols. We combine 16 point count datasets, controlling for differences in protocol and detection probabilities to estimate regional trends for 14 spruce-fir forest bird species across Northeastern and Midwestern United States, a vulnerable community threatened by numerous anthropogenic stressors and widely considered a priority for conservation. Our analyses indicated that four species considered as ecological indicators for this community, Bicknell's Thrush ( Catharus bicknelli ), Magnolia Warbler ( Setophaga magnolia ), Blackpoll Warbler ( Setophaga striata ) and Yellow-bellied Flycatcher ( Empidonax flaviventris ), each exhibited significant declines. Olive-sided Flycatcher ( Contopus cooperi ), a species of concern in parts of its range, and two additional species for which no previous concern existed, the Evening Grosbeak ( Coccothruastes vespertinus ) and the Gray Jay ( Perisoreus canadensis ), each also showed significant overall declines. Five out of nine species with sufficient data for analyses from Northeastern and Midwestern surveys showed significant differences in trends between these regions. Spruce-fir obligate species were more likely to decline significantly than species that use spruce-fir in addition to other habitat types. These results demonstrate the value of combining disparate data sources for analyzing regional patterns of population trends to confirm and extend conservation concern for some species and identify others for which additional attention may be needed.